2022
DOI: 10.5194/gmd-15-3447-2022
|View full text |Cite
|
Sign up to set email alerts
|

Empirical values and assumptions in the convection schemes of numerical models

Abstract: Abstract. Convection influences climate and weather events over a wide range of spatial and temporal scales. Therefore, accurate predictions of the time and location of convection and its development into severe weather are of great importance. Convection has to be parameterized in global climate models and Earth system models as the key physical processes occur at scales much lower than the model grid size. This parameterization is also used in some numerical weather prediction (NWP) models when convection is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 593 publications
0
15
0
Order By: Relevance
“…Given that simulated DCI, especially in complex terrain, needs improvement (Prein et al, 2015;Villalba-Pradas & Tapiador, 2022), relationships established in this study could better inform convection parameterization schemes. A topographical factor could be set to represent the probability of convection occurrence according to the elevation and relief amplitude of each model grid box.…”
Section: Discussionmentioning
confidence: 99%
“…Given that simulated DCI, especially in complex terrain, needs improvement (Prein et al, 2015;Villalba-Pradas & Tapiador, 2022), relationships established in this study could better inform convection parameterization schemes. A topographical factor could be set to represent the probability of convection occurrence according to the elevation and relief amplitude of each model grid box.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental questions about the origin of the in‐cloud air (Heus et al., 2008; Paluch, 1979), how mixing affects droplet size distribution (Khain & Pinsky, 2018; Prabhakaran et al., 2020; Tölle & Krueger, 2014), and how clouds affect the environmental radiative properties (Eytan et al., 2020; Koren et al., 2007; Marshak et al., 2006) are still open. Moreover, a significant part of the discrepancy between climate model results is attributed to cumulus mixing parameterization (Rio et al., 2019; Villalba‐Pradas & Tapiador, 2022). Hence, a better understanding of the mixing processes can significantly improve our climate understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The early studies suggested that the large‐scale, low‐level ascending motion, acting as a mechanic lifting mechanism, can help convection overcome the CIN to reach its LFC, and therefore, this dynamical effect of large‐scale vertical velocity has a positive impact on convective cloud development. Several convection schemes have explicitly incorporated the large‐scale vertical velocity in their trigger functions (see review of Villalba‐Pradas and Tapiador (2022)). Kuo (1974) required that large‐scale vertical velocity at 900‐mb be greater than a threshold to ensure that convective instability can be activated by large‐scale flow.…”
Section: Introductionmentioning
confidence: 99%